Equine grass sickness, but not botulism, causes autonomic and enteric neurodegeneration and increases soluble N‐ethylmaleimide‐sensitive factor attachment receptor protein expression within neuronal perikarya. (11th January 2016) - McGorum, B. C.; Scholes, S.; Milne, E. M.; Eaton, S. L.; Wishart, T. M.; Poxton, I. R.; Moss, S.; Wernery, U.; Davey, T.; Harris, J. B.; Pirie, R. S.
Summary: Reasons for performing study: Equine grass sickness (EGS) is of unknown aetiology. Despite some evidence suggesting that it represents a toxico‐infection with Clostridium botulinum types C and/or D, the effect of EGS on the functional targets of botulinum neurotoxins, namely the soluble N‐ethylmaleimide‐sensitive factor attachment receptor (SNARE) proteins, is unknown. Further, while it is commonly stated that, unlike EGS, equine botulism is not associated with autonomic and enteric neurodegeneration, this has not been definitively assessed. Objectives: To determine: 1) whether botulism causes autonomic and enteric neurodegeneration; and 2) the effect of EGS on the expression of SNARE proteins within cranial cervical ganglion (CCG) and enteric neuronal perikarya. Study design: Descriptive study. Methods: Light microscopy was used to compare the morphology of neurons in haematoxylin‐eosin stained sections of CCG and ileum from 6 EGS horses, 5 botulism horses and 6 control horses. Immunohistochemistry was used to compare the expression of synaptosomal‐associated protein‐25, synaptobrevin (Syb) and syntaxin within CCG neurons, and of Syb in enteric neurons, from horses with EGS, horses with botulism and control horses. The concentrations of these SNARE proteins in extracts of CCG from EGS and control horses were compared using quantitative fluorescent western blotting. Results: EGS, but not botulism, was associated with autonomic and enteric neurodegeneration and with increased immunoreactivity for SNARE proteins within neuronal perikarya. Quantitative fluorescent western blotting confirmed increased concentrations of synaptosomal‐associated protein‐25, Syb and syntaxin within CCG extracts from EGS vs. control horses, with the increases in the latter 2 proteins being statistically significant. Conclusions: The occurrence of autonomic and enteric neurodegeneration, and increased expression of SNARE proteins within neuronal perikarya, in EGS but not botulism, suggests that EGS may not be caused by botulinum neurotoxins. Further investigation of the aetiology of EGS is therefore warranted.